Effects of 6 weeks of different high-intensity interval and moderate continuous training on aerobic and anaerobic performance - Cavar, M.; Marsic, T.; Corluka, M.; Culjak, Z.; Cerkez Zovko, I.; Müller, A.; Tschakert, G.; Hofmann, P. (The Journal of Strength and Conditioning Research, 2019)
To provide practical data, we compared the training effects of 3 different programs, using a shuttle run stimulus, on aerobic and anaerobic performance, measured using the 20-m maximal shuttle run (Beep) test and 300-yd shuttle run, respectively. Forty-five physically trained men, with a mean age of 21.1 ± 1.8 years, participated. The 6-week, 12-session training programs included 2 high-intensity interval training (HIIT) protocols, with either a short (SH) or long (LH) shuttle run interval, and a continuous shuttle run (CON), which was used as a control. The training intensity was based on the maximal shuttle run speed (MASS), measured on the Beep test, to elicit the relevant values of the time to exhaustion (TTE). Short (SH) training was performed at 115-120%(MASS), with a 10-second work to 10-second rest scheme, and the number of repetitions to be completed set to 70% of each participant's maximum (~15 repetitions). LH training was performed at an intensity of 90-95%(MASS), with the duration set to 70%(TTE) (~4 minutes). For both SH and LH, 3 sets were completed at each session, with a 2-3 minutes of rest between sets. CON training consisted of continuous shuttle running for 35 minutes at an intensity of 70%(MASS). Both SH and LH yielded a large training effect (p < 0.01), with SH preferentially improving anaerobic performance and LH preferentially improving aerobic performance. No effect of CON training was identified. Our findings indicate that these different training protocols cannot be used interchangeably and that the Beep test is useful in prescribing the intensity and duration of HIIT.